FATE OF DOMINANT FOLLICLE IN SUMMl;R ANESTRUS BUFFALOES - GHUMAN, S P S; SINGH, JAGIR; HONPARKHE, M; DADARWAL, D; DHALIWAL, G S; SINGH, S T (The Indian Journal of Animal Reproduction, 2023)
During peak summer for a period of 24 days, anestrus (n=6) and cycling (n=5) buffaloes were subjected to transrectal ovarian ultrasonog raphy and jugular vein blood sampling on alternate days. During this period, anestrus buffaloes exhibited successive development of follicles which reached dominant phase (19 follicles, 12.6±0.3 mm diameter) but remained non-ovulatory. The diameter of ovulatory follicles (6 follicles) in cycling buffaloes was ·· 13.1 ±0. 8 mm. Plasma progesterone in an estrus and cycling buffaloes was 0.1 ±0.0 and 0. 71 ±0.03 ng/ml (p<0. 05 ), respectively. In brief, with the help of ultrasonography, it has been revealed for the first time that in the buffaloes displaying summer anestrus, ovarian follicular activity is going on although the dominant follicles that were able to attain ovulatory size failed to ovulate ahd regressed.